1-Amino-5-benzoyl-4-phenylpyrimidin-2(1H)-one - Dege, N; Sekerci, M; Çetin, A; Dinçer, M; Gülcan, M; Cansiz, A; Büyükgüngör, O (Int Union Crystallography, 2004)
In the title compound, C17H13N3O2, the two phenyl rings are approximately orthogonal. Intermolecular N - H ... O hydrogen bonds generate dimers. The crystal structure is stabilized by N - H ... O hydrogen bonds, and C - H ...pi and N - H ... pi interactions.